Targeted next-generation sequencing of TP53 in oral tongue carcinoma from non-smokers. Issue 1 (December 2016) - Faden, Daniel; Arron, Sarah; Heaton, Chase; DeRisi, Joseph; South, Andrew; Wang, Steven
Abstract Background Little is known regarding the etiology and genomic underpinnings of Oral Tongue Squamous Cell Carcinoma (OTSCC) in patients who lack traditional risk factors, yet the incidence is increasing. In particular, the rate, and role, of TP53 mutations in this cohort has been heavily debated in the literature. Methods Tumor DNA from forty-three non-smokers with OTSCC underwent next generation sequencing of TP53. Results Sixty percent of samples contained a TP53 mutation. The G > T transversion rate was 5.7 %. TP53 status did not differ by age. Conclusions OTSCC in non-smokers have TP53 mutation rates similar to other Head and Neck cancers yet these mutations do not appear related to carcinogen exposure based on the mutational spectrum and clinical history. The mechanisms driving tumorigenesis in this cohort, including mutations in TP53, remain elusive and further studies are needed.